Центральні образи та мотиви в поезії Сільвії Плат - Заболотна, Ольга (Видавництво Львівської політехніки, 2015)
This article analyzes the images of poetic works of Sylvia Plath. Plath's poetry gives a vision of life as enhanced by death. Her elegant and controlled style belied her images of anger, violence, and pain. Her finest work is the poetic realization of ultimate love and ultimate death.
Keywords: образ; концептуальна метафора; алюзія; жіноча ідентичність; поетичний контекст